Theoretical Aspects regarding Athletics and the Event of the Javelin Throw - L. Cuciorovschi; R.S. Enoiu (Editura Universitatii Transilvania din Brasov, 2023)
Standing out among the other three throwing events, the javelin throw is known to be one of the most spectacular events in the discipline of athletics. It usually takes place in the last two days of major world competitions due to its impressive show and thrilling changes that occur during the six attempts. This paper aims to present the theoretical aspects of this event through the research and study of the published literature and scientific work of specialists in this field. As the sports domain is one of a large content this paper is a contribution to a dynamic and expanding literature. Athletics and gymnastics are the sports disciplines that lie at the basis of all sports. The throwing technique of this event is constantly improving due to the specialized equipment and the continuous development of the technologies. In conclusion, the academic literature is expanding and the theoretical aspects are adapted to the discoveries.